Self-Care Lansia Hipertensi - praningsih, supriliyah; Maryati, Heni; Rosmaharani, Shanti (Jurnal Ilmiah Kesehatan Keperawatan, 2019)
Hypertension is heart disease that a life threatening and known as the silent killer. Right care was needed to control blood pressure in patients with hypertension to prevent further complications. This purpose determined the experience of elderly hypertension in daily self-care. The research design used a qualitative descriptive approach with participants in elderly hypertension patient and village midwives. Data collection had done by semi structured interviews, observations and field notes. Creswell's content analysis method was used to develop themes. The validity of the data used triangulation and member check. The results showed that the actions taken in an effort to self-care were to reduce salty eating, not drink coffee, and walk to refresh the mind and avoid stress and check blood pressure to the nearest midwife or auxiliary health center. Hypertension patients can treat themselves well to control of blood pressure to prevent complications. The surrounding community can help to reduce stress in patients with economic support to help patients with low socioeconomic will get survival. The researcher can examine the analysis of the main factors causing hypertension and connecting with elderly self-care with hypertension